The agreement of existential haber in Mexico City - Lastra, Yolanda; Martín Butragueño, Pedro (Boletín de Filología, 2017)
This paper studies the singular or plural agreement between Spanish verb "haber" with existential meaning and its plural argument, in 108 interviews collected in Mexico City as a part of a sociolinguistic corpus structured by age, gender and educational level. All relevant data (633) are considered. For the analysis, the proposed methodology in the “Project for the sociolinguistic study of Spanish from Spain and from America (PRESEEA)” is followed, using a wide range of linguistic and social variables. The results are subjected to rigorous statistical analysis and compared with those obtained in other studies. The singular/plural alternative has received considerable attention in the field of study of linguistic variation in Spanish. Mexico City Spanish is grouped with other conservative areas.